Studi Implementasi Good Governance Pemerintahan Daerah Kabupaten Bone Bolango - Trisusanti Lamangida (Universitas Muhammadiyah Gorontalo, 2017)
Some disadvantages show that the implementation of participation, transparency (transparency), responsiveness, and accountability principles in Bone Bolango County Government Office have not fulfilled the public expectation. Whereas the implementation or application of the principles of good governance is an important aspect in supporting the achievement of the objectives of the Regional Government. The purpose of this research is to know the application of Good Governance principles in Bone Bolango Regency Government. The research method used is qualitative approach with descriptive research type. The results of this study indicate that the implementation of the principle of Good Goveranance on Regional Government of Bone Bolango Regency has been running well but not yet maximal. There are still weaknesses in the implementation of good governance namely the transparency principle of weaknesses of government management transparency information has not been well developed. Beberapa kelemahan menunjukkan bahwa penerapan prinsip partisipasi (participation), transparansi (transparancy), daya tanggap (responsiveness), dan akuntabilitas (accountability) di Kantor Pemerintahan Kabupaten Bone Bolango belum memenuhi harapan masyarakat. Padahal implementasi atau penerapan prinsip-prinsip good governance merupakan aspek penting dalam mendukung pencapaian tujuan Pemerintah Daerah. Tujuan Penelitian ini ialah untuk mengetahui penerapan prinsip-prinsip Good Governance di Pemerintah Kabupaten Bone Bolango. Metode penelitian yang digunakan ialah pendekatan kualitatif dengan jenis peelitian deskriptif. Hasil dari penelitian ini menunjukkan bahwa pelaksanaan prinsip Good Goveranance pada Pemerintahan Daerah Kabupaten Bone Bolango sudah berjalan dengan baik tetapi belum maksimal. Masih terdapat kelemahan dalam implementasi good governance yakni prinsip transparansi kelemahan informasi manajemen transparansi pemerintahan belum berkembang dengan baik.